1999
DOI: 10.1016/s0014-5793(99)01163-1
|View full text |Cite
|
Sign up to set email alerts
|

Calorie restriction increases Fas/Fas‐ligand expression and apoptosis in murine splenic lymphocytes

Abstract: One-month-old male ICR mice were fed a nutritionally adequate, semipurified diet, either ad libitum (AL) or calorie restricted (CR) (40% less food) for 6 months and were killed to obtain spleens. Flow cytometric analysis revealed increased proportions of both CD4+ and CD8+ T cells in CR-fed mice compared to AL-fed mice. The T cell subsets of CR-fed mice were also found to have higher levels of plasma membrane Fas receptor expression. Similarly, Fas-ligand (Fas-L) expression was higher in anti-CD3-stimulated CD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
1

Year Published

2001
2001
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 51 publications
2
8
1
Order By: Relevance
“…Previous studies have reported that CR administered to lean or obese rodents increases total T cell population and both CD4 + and CD8 + subpopulations [10,32,33]. Consistent with these previous results, in the current study, which focused on CD4 + T cells and their subpopulations, we found that spleens from CR mice had higher percentages of CD4 + T cells.…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies have reported that CR administered to lean or obese rodents increases total T cell population and both CD4 + and CD8 + subpopulations [10,32,33]. Consistent with these previous results, in the current study, which focused on CD4 + T cells and their subpopulations, we found that spleens from CR mice had higher percentages of CD4 + T cells.…”
Section: Discussionsupporting
confidence: 92%
“…Similar to ours and several other previous reports (Gartner et al, 1992;Luan et al, 1995;Reddy et al, 1999), the present study also showed that CR maintained a significantly higher proportion of CD4 ϩ cells compared to AL feeding. With age, CD8 ϩ cells were increased in AL-fed mice, but CR prevented the ageassociated increase of CD8 ϩ cells.…”
Section: (E-h) Young (A E) and Old (C G) Ad Libitum (Al); Young (Bsupporting
confidence: 93%
“…Further, we also observed strain variation in apoptosis in CR-fed mice. We have previously reported increased apoptosis in CR-fed MRL/lpr and a randomly bred ICR strain of mice with or without differences in Fas and Fas-mediated apoptosis (Luan et al, 1995;Reddy et al, 1999). However, our recent studies show differences in apoptosis between C57BL/6J and Balb/C mice maintained on an AL-or CR-fed diet.…”
Section: (E-h) Young (A E) and Old (C G) Ad Libitum (Al); Young (Bmentioning
confidence: 73%
See 1 more Smart Citation
“…Moreover, the reports of apoptosis induction by ER in various cancer models are in marked contrast to reports in experimental models of aging that ER inhibits apoptosis (25)(26)(27). This situation underscores the importance of identifying the mechanisms that account for changes in rates of apoptosis induced by ER under both physiological and patho-physiological conditions.…”
Section: Discussionmentioning
confidence: 89%